1998
DOI: 10.1007/s11626-998-0125-7
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin production by cultured human lung fibroblasts in three-dimensional collagen gel culture

Abstract: In vivo, fibroblasts are distributed in a three-dimensional (3-D) connective tissue matrix. Fibronectin is a major product of fibroblasts in routine cell culture and is thought to regulate many aspects of fibroblast biology. In this context, we sought to determine if the interaction of fibroblasts with a 3-D matrix might affect fibronectin production. To examine this hypothesis, fibronectin production by fibroblasts cultured in a 3-D collagen gel or on plastic dishes was measured by ELISA. Fibroblasts in 3-D g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Only the fibronectin released into the culture media was measured in the current study. Previous studies have demonstrated that approximately one-third of fibronectin is released into the culture medium in three-dimensional culture collagen gel, and more than half is released into the culture media in monolayer culture (30). Thus the absorption amounts measured do not reflect the total fibronectin production.…”
Section: Discussionmentioning
confidence: 90%
“…Only the fibronectin released into the culture media was measured in the current study. Previous studies have demonstrated that approximately one-third of fibronectin is released into the culture medium in three-dimensional culture collagen gel, and more than half is released into the culture media in monolayer culture (30). Thus the absorption amounts measured do not reflect the total fibronectin production.…”
Section: Discussionmentioning
confidence: 90%
“…The interactions between fibroblasts, their secreted products, and the surrounding matrix are important in tissue remodeling for the development of scar formation and fibrosis. 15 It could be a response to injury of the gland. Type III collagen also showed an expression similar to that of fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…For the culture of fibroblasts in vitro , hydrogels have been formed from naturally-derived native ECM components, such as collagen, fibrin, and hyaluronic acid, 8 or synthetic materials functionalized with bioactive moieties, such as polyacrylamide modified with whole ECM proteins 9 or poly(ethylene glycol) (PEG) modified with protein mimetic peptides. 10 As will be elaborated below (Section B), fibroblasts traditionally have been cultured in fibrin 11,12 and type I collagen (collagen I) 13,14 to mimic the matrix present during different phases of wound healing. In these models, cell proliferation, activation, matrix synthesis, and contractility have been examined as signs of fibroblast activation.…”
Section: Introductionmentioning
confidence: 99%